2013
DOI: 10.1007/s10072-012-1269-5
|View full text |Cite
|
Sign up to set email alerts
|

Italian multicentre observational study of the prevalence of CCSVI in multiple sclerosis (CoSMo study): rationale, design, and methodology

Abstract: Chronic cerebro-spinal venous insufficiency (CCSVI) has been proposed as a “congenital malformation” implicated in the pathogenesis of multiple sclerosis (MS). However, numerous studies failed to confirm its presence in MS patients. This paper presents the rationale, design, and methodology adopted in the CoSMo study, conducted with the aim of verifying whether or not CCSVI is linked to MS. The primary endpoint of the CoSMo study is to compare the prevalence of CCSVI in patients with MS versus patients affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
0
19
1
Order By: Relevance
“…The rationale, study design and methodology were recently published. 30 The primary objective of the CoSMo study, named after the Italian words ''CCSVI: Studio Osservazionale Sclerosi Multipla e OND,'' which translates to Observational Study of the prevalence of CCSVI in multiple sclerosis and OND, is to compare the prevalence of CCSVI in MS patients, healthy controls (HCs) and patients with other neurological diseases (ONDs). The secondary objectives are the evaluation of the correlation of CCSVI with demographic and clinical parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The rationale, study design and methodology were recently published. 30 The primary objective of the CoSMo study, named after the Italian words ''CCSVI: Studio Osservazionale Sclerosi Multipla e OND,'' which translates to Observational Study of the prevalence of CCSVI in multiple sclerosis and OND, is to compare the prevalence of CCSVI in MS patients, healthy controls (HCs) and patients with other neurological diseases (ONDs). The secondary objectives are the evaluation of the correlation of CCSVI with demographic and clinical parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Comi et al [7] published the results of their "Italian multicenter observational study of the prevalence of CCSVI in multiple sclerosis" (CoSMo study) which attempted to validate the presence of CCSVI in MS using Zamboni's DU criteria. He CoSMo group found that in MS patients, the presence of CCSVI was 3.26%.…”
Section: Discussionmentioning
confidence: 99%
“…There are now two recent publications of good and unbiased quality, studying approximately 2000 patients, that show that CCSVI has no higher prevalence in MS than in any other group of patients without MS or healthy volunteers, which proves the hypothesis of CCSVI and venous congestion in relation to MS to be wrong [2,3]. Next to the five Zamboni criteria, many followers were encouraged by the observation that some MS patients responded positively to the balloon dilatation treatment.…”
Section: Ccsvimentioning
confidence: 99%
“…Others have been less cautious, focusing instead more on the perceived opportunities of this new technique. Now that two major studies [2,3] have shown that CCSVI does not exist-not in MS and not in any other group, such as siblings of MS patients and healthy volunteers-it is perhaps time to draw some conclusions regarding the introduction of future new and socalled promising interventional procedures.…”
Section: Introductionmentioning
confidence: 99%